Gold and Silver as Safe Havens: A Fractional Integration and Cointegration Analysis - Guglielmo Maria Caporale; Luis A. Gil-Alana (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper investigates whether gold and silver can be considered safe havens by examining their long-run linkages with 22 stock price indices. More specifically, the stochastic properties of the differential between gold/silver prices and 22 stock indices are analysed applying fractional integration/cointegration methods to daily data, first for a sample from January 2010 until December 2019, then for one from January 2020 until July 2022 which includes the Covid-19 pandemic. The results can be summarised as follows. In the case of the pre-Covid-19 sample ending in December 2019, mean reversion is found for the gold price differential vis-à-vis BEF, BSE, CAC, DOW, KLS, KS1, MXX, N100, NAS, NYA and SP5 and for both differentials vis-à-vis CAC, KLS and N100, i.e. the evidence is mixed on whether these precious metals can be seen as safe havens, though it appears that this property characterises gold in a slightly higher number of cases. By contrast, when using the sample starting in January 2020, the evidence in favour of gold and silver as possible safe havens is pretty conclusive since mean reversion is only found in a single case, namely that of the gold differential vis-à-vis NZX.
Keywords: C22; C32; F30; F36; G01; G15; 330; gold and silver; hedge; safe heaven; fractional integration and cointegration